Effects of nutritional conditions on growth and biochemical composition of Tetraselmis sp. Issue 1 (December 2017) - Dammak, Mouna; Hadrich, Bilel; Miladi, Ramzi; Barkallah, Mohamed; Hentati, Faiez; Hachicha, Ridha; Laroche, Céline; Michaud, Philippe; Fendri, Imen; Abdelkafi, Slim
Abstract Background This study aimed to maximize biomass concentration, biomass productivity and biochemical composition of the marine microalgaTetraselmis sp. Methods In the current study, Box-Behnken Design was used to model the effect of NaNO3, NaH2 PO4, metals and vitamins in the F/2 medium on the growth, total chlorophylls, carotenoids and starch contents. The total chlorophylls content was quantified by spectrophotometry. The FT-IR spectroscopy was used to estimate the biochemical compositions ofTetraselmis sp. grown under both optimized medium culture for starch production and standard culture medium. Results Finalized NaNO3 (1.76 mM), NaH2 PO4 (0.018 mM), metals (1500 μL.L−1 ) and vitamins (312.5 μL.L−1 ) concentrations, generated an increase in biomass concentration up to 5.72 g.L−1 which contributed to an increase about 2.4-fold than that of the standard conditions of biomass productivity (408.57 mg.L−1 .day−1 ). The maximum value of carotenoids content (0.3 mg.g DW−1 ) was achieved at the highest level of all factors. The total chlorophylls content reached also its maximum (5.18 mg.g DW−1 ) at high nitrate (1.76 mM), phosphate (0.054 mM), metals and vitamins concentrations, while the maximum starch content (42% DW) was achieved with low nitrate and phosphate concentrations (0.58 mM and 0.027 mM) and with metals and vitamins limitations. Thus, the nitrogen, phosphorus, metals and vitamins limitations led to divert the metabolism for the starch biosynthesis. Conclusions The high biomass concentration productivity and starch production makeTetraselmis sp. strain a good candidate for biotechnological applications.